TRANSAKSI JUAL BELI ONLINE PERSPEKTIF HUKUM ISLAM - IRMAWATI ARFAT (IAIN BONE, 2021)
AbstractThis article discusses buying and selling online from the perspective of Islamic law. This is important to discuss because seeing the proliferation of online buying and selling systems in the present, there needs to be a special study related to this. Because also buying online is likely to have gharar elements in it while gharar in Islam is prohibited because of the uncertainty of the goods to be bought and sold. The results of this study indicate that the systems used in online buying and selling are called Dropshipping and Reselling, in terms of the application of online buying and selling between bai 'al-ma'dum and bai salam if linked in bai' al-ma'dum online buying and selling is prohibited. its application is because the object of the goods being traded is unclear and contains gharar elements while inline buying and selling with the application of bai salam is allowed because of the guarantee to bring goods in accordance with the agreed time. If viewed from the perspective of Islamic law, buying and selling online is allowed as long as there is no argument against it and it is in accordance with the provisions of the Sharia in buying and selling. Where the seller and the buyer are consensual and mutually willing. Besides that, the seller and the buyer are open to each other regarding information on goods and their prices so that there is no gharar element in them. This buying and selling is legally permissible because it is almost the same as the salam contract and the scholars agree that the sale and purchase of greetings is permissible.Keywords: Buying and Selling; Gharar; Islamic Law.AbstrakArtikel ini membahas mengenai jual beli online perspektif hukum Islam. Hal ini penting untuk dibahas karena melihat maraknya sistem jual beli online di masa sekarang sehingga perlu ada pengkajian khusus terkait hal ini. Karena jual beli online berpotensi besar terdapat unsur gharar di dalamnya. Sedangkan gharar dalam Islam dilarang karena adanya ketidakpastian terhadap barang yang akan diperjual belikan. Hasil penelitian ini menunjukkan bahwa sitem yang digunakan dalam jual beli online disebut dengan Dropshipping dan Reselling, dilihat dari segi penerapan jual beli online antara bai’ al-ma’dum dan bai salam jika dikaitkan dalam jual beli online bai’ al-ma’dum dilarang penerapannya karena objek barang yang diperjual belikan tidak jelas adanya dan mengandung unsur gharar. Sedangkan jual beli online dengan penerapan bai salam dibolehkan karena adanya jaminan mendatangkan barang sesuai dengan waktu yang disepakati. Jika ditinjau dari perspektif hukum Islam, jual beli online ini dibolehkan selama tidak ada dalil yang melarangnya dan sesuai ketentuan syariat dalam jual beli. Dimana antara penjual dan pembeli berlaku antara suka sama suka dan saling rela. Selain itu, antara penjual dan pembeli saling terbuka mengenai informasi barang dan harganya sehingga tidak ada unsur gharar di dalamnya. Jual beli ini dibolehkan hukumnya karena hampir sama dengan akad salam dan para ulama menyepakati bahwa jual beli salam itu dibolehhkan.Kata Kunci: Jual beli; Gharar; Hukum Islam.